Strategies to overcome the hurdles to treat fibrosis, a major unmet clinical need - Nanchahal, J; Hinz, B (National Academy of Sciences, 2016)
Fibroproliferative disorders are estimated to contribute to 45% of deaths in the United States (1). Although this huge number includes atherosclerosis, the biggest killer in the developed world, less common conditions, such as idiopathic pulmonary fibrosis, fibrosis of the liver and kidney, and systemic sclerosis are also associated with high mortality. Localized fibrotic conditions—including endometriosis, abdominal adhesions, frozen shoulder, and Dupuytren’s disease—which receive much less attention, also cause considerable morbidity and together affect more than 10% of the population.